She walks in beauty - Mitchell, Siri L., 1969- (Bethany House, 2010)
For a young society woman seeking a favorable marriage in the late 1890s, debutante Clara Carter has been given one goal: secure the affections of the city's most eligible bachelor. But when a man appears who seems to love her simply for who she is, and gossip backlash turns ugly, Clara realizes it's not just her heart at stake-- the future of her family depends on how she plays the game.